2016
DOI: 10.14348/molcells.2016.2308
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA CCAT1 Acts as a Competing Endogenous RNA to Regulate Cell Growth and Differentiation in Acute Myeloid Leukemia

Abstract: Long non-coding RNAs (lncRNAs) are involved in multiple cellular events, as well as in tumorigenesis. Colon cancer-associated transcript-1 (CCAT1) gene encodes an lncRNA whose over-activation was observed in an expanding list of primary human solid tumors and tumor cell lines, however its biological roles in acute myeloid leukaemia (AML) has not been reported yet at present. In this study, the aberrant upregulation of CCAT1 was detected in French-American-British M4 and M5 subtypes of adult AML patients. By ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 37 publications
3
67
0
Order By: Relevance
“…UCA1 silencing by short-hairpin RNA transduction results in a significant reduction of cell proliferation, with an increase in the G1 phase and a decrease in the S phase. Another example is lncRNA CCAT1, which can coordinate the proliferation and differentiation of AML cells [25]. Overexpression and knockdown experiments demonstrate that CCAT1 inhibits the PMA-induced monocytic differentiation as well as promotes the proliferation of AML-derived HL60 cells [25].…”
Section: The Roles Of Lncrnas In Myeloid Leukemiamentioning
confidence: 99%
See 3 more Smart Citations
“…UCA1 silencing by short-hairpin RNA transduction results in a significant reduction of cell proliferation, with an increase in the G1 phase and a decrease in the S phase. Another example is lncRNA CCAT1, which can coordinate the proliferation and differentiation of AML cells [25]. Overexpression and knockdown experiments demonstrate that CCAT1 inhibits the PMA-induced monocytic differentiation as well as promotes the proliferation of AML-derived HL60 cells [25].…”
Section: The Roles Of Lncrnas In Myeloid Leukemiamentioning
confidence: 99%
“…Another example is lncRNA CCAT1, which can coordinate the proliferation and differentiation of AML cells [25]. Overexpression and knockdown experiments demonstrate that CCAT1 inhibits the PMA-induced monocytic differentiation as well as promotes the proliferation of AML-derived HL60 cells [25]. As to apoptosis of AML cells, Xing et al [27] found that HOTAIR knockdown inhibits cell growth and colony formation, and also induces the apoptosis of AML cells [27].…”
Section: The Roles Of Lncrnas In Myeloid Leukemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, lncRNAs can alter the post-transcriptional regulation of mRNA, cellular signaling, and protein activity through allosteric regulation45. Some lncRNAs can act as microRNA sponges to reduce the amount of microRNA available to target genes678. To obtain a better understanding of regulatory networks in cell, it is important to understand the function of each lncRNA.…”
mentioning
confidence: 99%